Focusing on DC cells to optimize the prediction of prognosis and innovative treatment strategies for colon cancer - Chaobo Chen; Zhengqiu Wang; Bo Xi; Zipeng Xu; Chunlong Zhao; Weidong Hu; Chen Ge; Genxi Tong; Fengjun Cai; Mingli Zhou; Yihang Yuan (Scientific Reports)
Abstract Colon adenocarcinoma (COAD) is a leading cause of cancer-related mortality worldwide, with immune cells, particularly dendritic cells (DCs), playing an essential part in the advancement of tumors and immunotherapy response. However, the prognostic significance of genes associated with dendritic cells (DCRGs) in COAD remains underexplored. This study aims to identify DCRGs, construct a risk scoring system, and evaluate its prognostic and therapeutic implications. Data from single-cell RNA sequencing (scRNA-seq) of COAD tissues were examined for the detection of DCRGs. Transcriptomic and clinical data from TCGA and GEO were used to construct a DC Related Index (DCRI) via WGCNA, differential expression, univariate Cox regression, and LASSO-Cox analysis. The DCRI was validated in internal and external cohorts. Immune infiltration, MSI status, immune checkpoint expression, and drug sensitivity were analyzed to assess clinical relevance. Functional experiments were performed to investigate the role of PPP2CB in COAD progression. A five-gene signature (CTSD, DAPK1, TIMP1, TBXAS1, PPP2CB) was identified and used to construct a DCRI. The DCRI effectively stratified patients into high- and low-DCRI groups, with significant survival differences. High-DCRI patients exhibited distinct immune infiltration patterns, higher MSI scores, and increased sensitivity to immunotherapy. Functional experiments revealed PPP2CB as a protective factor, with its downregulation inhibits COAD cell proliferation, migration, and invasion. We developed a novel DCRI that accurately predicts COAD prognosis and immunotherapy response. PPP2CB was identified as a potential therapeutic target, offering new insights for personalized COAD treatment strategies.